Cultures of energy : power, practices, technologies - Strauss, Sarah; Rupp, Stephanie; Love, Thomas F. (Left Coast Press, 2013)
"This path-breaking volume explores cultures of energy, the underlying but under-appreciated dimensions of both crisis and innovation in resource use around the globe. Theoretical chapters situate pressing energy issues in larger conceptual frames, and ethnographic case studies reveal energy as it is imagined, used, and contested in a variety of cultural contexts. Contributors address issues including the connection between resource flows and social relationships in energy systems; cultural transformation and notions of progress and collapse; the blurring of technology and magic; social tensions that accompany energy contraction; and sociocultural changes required in affluent societies to reduce dependence on fossil fuels. Each of five thematic sections concludes with an integrative and provocative conversation among the authors."--Publisher's website.